Adverse events of colonoscopy in a colorectal cancer screening program with fecal immunochemical testing: a population-based observational study - Denis, Bernard; Gendre, Isabelle; Weber, Sarah; Perrin, Philippe (Endoscopy International Open, 2021)
Background and study aims The aim of this study was to assess adverse events (AEs) associated with colonoscopy in the French colorectal cancer screening program with fecal occult blood test (FOBT).Patients and methods A retrospective cohort study was performed of all colonoscopies performed from 2015 to 2018 for a positive fecal immunochemical test (FIT) in patients aged 50 to 74 years within the screening program in progress in Alsace, part of the French program. AEs were recorded through prospective voluntary reporting by community gastroenterologists and retrospective postal surveys addressed to individuals screened. They were compared with those recorded in the previous program following colonoscopies performed from 2003 to 2014 for a positive guaiac-based FOBT (gFOBT). Results Of 9576 colonoscopies performed for a positive FIT, 6194 (64.7 %) were therapeutic. Overall, 180 AEs were recorded (18.8 ‰, 95 % CI 16.1–21.5), 114 of them (11.9 ‰, 95 % CI 9.7–14.1) requiring hospitalization, 55 (5.7‰, 95 % CI 4.2–7.3) hospitalization > 24 hours, and eight (0.8 ‰, 95 % CI 0.3–1.4) surgery. The main complications requiring hospitalization were perforation (n = 18, 1.9 ‰, 95 % CI 1.0–2.7) and bleeding (n = 31, 3.2 ‰, 95 % CI 2.1–4.4). Despite a significant increase in several risk factors for complication, the rate of AEs remained stable between gFOBT and FIT programs. Overall, we observed one death (1/27,000 colonoscopies) and three splenic injuries. Conclusions The harms of colonoscopy in a colorectal cancer screening program with FIT are more frequent than usually estimated. This study revealed six AEs requiring hospitalization > 24 hours (three bleeds, two perforations), one necessitating surgery, and 50 minor complications per 1000 colonoscopies.